Calcium-induced folding and stabilization of cold-active RTX lipase from Pseudomonas sp. strain AMS8 - Mohd Ali, Nur Shidaa (2020)
Repeat-in-Toxin (RTX) represents a broad family of protein produced by Gram-negative bacteria. RTX protein consists of RTX parallel β-roll motif repeat structure. Previously, AMS8 lipase from Antarctic Pseudomonas fluorescens strain AMS8 was classified as RTX lipase. The previous study has been reported the Ca2+ ions play a role in the formation of RTX parallel β-roll motif repeat structure and involve in the folding and stabilization of many RTX protein. However, the contributions of Ca2+ ions towards the folding and stabilization of AMS8 lipase have not been understood. It is hypothesized that the Ca2+ ions induce the formation of RTX parallel β-roll motif repeat structure and involve in the folding and stabilization of AMS8 lipase. Thus, this research aimed to examine the influence of Ca2+ ion towards the activity, folding and stabilization of AMS8 lipase through the in-silico approach and various biophysical characterizations. AMS8 lipase contains six Ca2+ ions (Ca1, Ca2, Ca3, Ca4, Ca5 and Ca6) and RTX parallel β-roll motif repeat structures. In-silico studies were done to analyze the structural conformational changes of the AMS8 lipase structure using molecular docking and molecular dynamics (MD) simulation. As a result, metal ion docking analysis gives high binding energy, especially for Ca4 and Ca5. To further analyze the function of each Ca2+ ions, MD simulation was performed. The removal of Ca3, Ca4 and Ca5 caused the AMS8 lipase structure to become unstable and unfolded. These suggested that Ca3, Ca4 and Ca5 were involved in the stabilization and folding of the RTX parallel β-roll motif repeat structure.AMS8 lipase activity was increased in the presence of CaCl2, where the optimum CaCl2 concentration was detected at 80 mM. To further confirm the contribution of Ca2+ ion, various biophysical characterizations using circular dichroism (CD), fourier-transform infrared (FTIR), intrinsic and extrinsic fluorescence, dynamic light scattering (DLS) and isothermal titration calorimetry (ITC) were performed. The far-UV CD and FTIR analyses suggested that the secondary structure content was improved with the addition of CaCl2. Intrinsic and extrinsic fluorescence analysis showed that the presence of CaCl2 increased protein folding and compactness. DLS analysis suggested the AMS8 lipase became aggregated at a high concentration of CaCl2. The binding constant (Kd) value from the ITC analysis proved that the Ca2+ ion was tightly bound to the AMS8 lipase. In conclusion, in-silico approach and various biophysical characterizations revealed that Ca2+ ions play essential roles in the activity, folding and stability of the AMS8 lipase. Furthermore, Ca2+ ions also induced the folding of the RTX parallel β-roll motif repeat structure and played a crucial role in the folding and stabilization purposes of the whole AMS8 lipase structure.